New records of Ichthyostraca Zrzavý, Hypša & Vlášková, 1997 (Pancrustacea) from Mexico with an annotated checklist of North America - Lagunas-Calvo, Omar; García-Prieto, Luis; Osorio-Sarabia, David; León-Règagnon, Virginia; Oceguera-Figueroa, Alejandro (Zootaxa, 2020)
In this work, we document for the first time four species of Ichthyostraca in Mexico, one Branchiura: Argulus foliaceus (fish parasite), and three Pentastomida: Porocephalus clavatus (reptile parasite), Raillietiella hebitihamata (reptile parasite) and Raillietiella orientalis (frog parasite). In addition, a total of 11 new host records and 16 new localities are presented for Ichthyostraca in Mexico. Based on the compilation of published information and on specimens deposited in scientific collections, the first checklist of Ichthyostraca from North America (Canada, United States of America and Mexico) is compiled. To March 2019, records of Ichthyostraca from North America include 64 species and 8 undetermined taxa, parasitizing 293 host species (64 of them identified only to a supra-specific level) in 77 provinces and states (8 from Canada, 47 from the USA, and 22 from Mexico). The subclass Branchiura is represented by 1 order, 1 family, 1 genus, 35 species and 1 undetermined taxa; the subclass Pentastomida includes records of 4 orders, 9 families, 14 genera, 29 species and 7 undetermined taxa. Ten species reported in this work are thought to be introduced into North America with only a few records of them parasitizing native hosts. This checklist summarizes the available records of this class of crustaceans in North America and represents a base line for future studies.